The Mw = 6.3, November 21, 2004, Les Saintes earthquake (Guadeloupe): Tectonic setting, slip model and static stress changes - Jacques, E. (2012)
On November 21, 2004, a magnitude 6.3 earthquake occurred offshore, 10 km south of Les Saintes archipelago in Guadeloupe (French West Indies). There were more than 30000 aftershocks recorded in the following two years, most of them at shallow depth near the islands of the archipelago. The main shock and its main aftershock of February 14, 2005 (Mw = 5.8) ruptured a NE-dipping normal fault (Roseau fault), mapped and identified as active from high-resolution bathymetric data a few years before. This fault belongs to an arc-parallel en echelon fault system that follows the inner edge of the northern part of the Lesser Antilles arc, accommodating the sinistral component of oblique convergence between the North American and Caribbean plates. The distribution of aftershocks and damage (destruction and landslides) are consistent with the main fault plane location and attitude. The slip model of the main shock, obtained by inverting jointly global broadband and local strong motion records, is characterized by two main slip zones located 5 to 10 km to the SE and NW of the hypocenter. The main shock is shown to have increased the Coulomb stress at the tips of the ruptured plane by more than 4 bars where most of the aftershocks occurred, implying that failures on fault system were mainly promoted by static stress changes. The earthquake also had an effect on volcanic activity since the Boiling Lake in Dominica drained twice, probably as a result of the extensional strain induced by the earthquake and its main aftershock.